2023
DOI: 10.1088/1402-4896/ace0df
|View full text |Cite
|
Sign up to set email alerts
|

Mode-locked orbits, doubling of invariant curves in discrete Hindmarsh-Rose neuron model

Abstract: Similar to period-doubling bifurcation of fixed points, periodic orbits, it has been found since 1980's that a corresponding doubling bifurcation can also be found in the case of quasiperiodic orbits. Doubling bifurcations of quasiperiodic orbits has an important consequence on the dynamics of the system under consideration. Recently, it has been shown that subsequent doublings of quasiperiodic closed invariant curves leads to the formation of Shilnikov attractors. In this contribution, we illustrate for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In order to have a deeper understanding of neuronal networks, researchers in various fields have explored the characteristics and dynamical behavior of neuron models from the perspective of different mathematical functions and analyses. [1][2][3][4][5][6][7][8][9][10] Memristors are the fourth basic passive circuit element after resistors, inductors and capacitors. It can be seen from Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In order to have a deeper understanding of neuronal networks, researchers in various fields have explored the characteristics and dynamical behavior of neuron models from the perspective of different mathematical functions and analyses. [1][2][3][4][5][6][7][8][9][10] Memristors are the fourth basic passive circuit element after resistors, inductors and capacitors. It can be seen from Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This study helps advance our understanding of complex networks and the process of neuron firing. Muni et al 2022 considered nodal and network behaviours considering electromagnetic flux coupling show the effect of magnetic flux on the phenomenon of bistability and the presence of periodic and chaotic attractor [23][24][25][26]. More recenlty, another authors analyzed the effects of electromagnetic flux on the discrete Chialvo neuron model, and shown that the model can exhibit rich dynamical behaviors such as multistability.…”
Section: Introductionmentioning
confidence: 99%
“…More recenlty, another authors analyzed the effects of electromagnetic flux on the discrete Chialvo neuron model, and shown that the model can exhibit rich dynamical behaviors such as multistability. The impact of magnetic flux is proved on the bifurcation diagrams, Lyapunov exponent diagram, phase portraits, basins of attraction [24][25][26][27]. Recent studies have shown that magnetic induction can destroy or accelerate enzymatic reactions based on memristors [21,28].…”
Section: Introductionmentioning
confidence: 99%